2011
DOI: 10.2478/v10006-011-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Hopf bifurcation analysis for a Lotka-Volterra predator-prey model with two delays

Abstract: In this paper, a two-species Lotka-Volterra predator-prey model with two delays is considered. By analyzing the associated characteristic transcendental equation, the linear stability of the positive equilibrium is investigated and Hopf bifurcation is demonstrated. Some explicit formulae for determining the stability and direction of Hopf bifurcation periodic solutions bifurcating from Hopf bifurcations are obtained by using normal form theory and center manifold theory. Some numerical simulations for supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Secondly, compared with continuous-time models, the advantage they offer is that they are generally more direct, more convenient and more accurate to formulate. Thirdly, recent works have shown that for discrete-time models the dynamics can produce a much richer set of patterns than those observed in continuous-time models (Busłowicz, 2010;Busłowicz and Ruszewski, 2012;Duda, 2012;Feedman, 1980;Holling, 1965;Huang and Xiao, 2004;Hsu, 1978;Raja et al, 2011;Xu et al, 2011;Zhang et al, 2011). At last, we can get more interesting dynamical behaviors and more accurate numerical simulations results from the discrete-time models; moreover, numerical simulations of continuous-time models are obtained by discretizing the models.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, compared with continuous-time models, the advantage they offer is that they are generally more direct, more convenient and more accurate to formulate. Thirdly, recent works have shown that for discrete-time models the dynamics can produce a much richer set of patterns than those observed in continuous-time models (Busłowicz, 2010;Busłowicz and Ruszewski, 2012;Duda, 2012;Feedman, 1980;Holling, 1965;Huang and Xiao, 2004;Hsu, 1978;Raja et al, 2011;Xu et al, 2011;Zhang et al, 2011). At last, we can get more interesting dynamical behaviors and more accurate numerical simulations results from the discrete-time models; moreover, numerical simulations of continuous-time models are obtained by discretizing the models.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely suggested that negative feedback loop can induce biochemical oscillation [9–12], and the functional mechanism of such feedback loop in the p53 network has been studied by many researchers [6, 13–15]. It was reported that p53 dynamics depend on the p53‐murine double minute 2 (Mdm2) and ataxia telangiectasia mutated (ATM)‐wild‐type p53‐induced phosphatase 1 (ATM‐p53‐Wip1) negative feedback loops [16].…”
Section: Introductionmentioning
confidence: 99%
“…Predator-prey systems are very important in population dynamics and have been investigated by many authors [2,4,14,15,18,23,24]. It is well known that there are many species whose individual members have a life history that takes them through immature stage and mature stage.…”
Section: Introductionmentioning
confidence: 99%